2012
DOI: 10.1016/j.cis.2012.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulsion stability: Experimental evaluation of the flocculation rate from turbidity measurements

Abstract: The coalescence of liquid drops induces a higher level of complexity compared to the classical studies about the aggregation of solid spheres. Yet, it is commonly believed that most findings on solid dispersions are directly applicable to liquid mixtures. Here, the state of the art in the evaluation of the flocculation rate of these two systems is reviewed. Special emphasis is made on the differences between suspensions and emulsions. In the case of suspensions, the stability ratio is commonly evaluated from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 140 publications
0
35
0
4
Order By: Relevance
“…Such behavior leading to thermodynamic instability was observed to be least with NEs stored at 22 ± 1 C, which indicated that coalescence could be controlled by storage of formulation at this temperature. The NEs stored at 4 ± 1 C exhibited higher increase in droplet size (coalescence) which might be attributed to the fact that at low temperature, NE droplets tend to aggregate/coalesce (Rahn-Chique et al, 2012). Jiang et al, have reported an increase in particle size up to 100 nm at room temperature in a three months stability study of nanoemulsion but they did not find any variation in the entrapment efficiency (Jiang et al, 2013).…”
Section: Stability Of Nesmentioning
confidence: 97%
“…Such behavior leading to thermodynamic instability was observed to be least with NEs stored at 22 ± 1 C, which indicated that coalescence could be controlled by storage of formulation at this temperature. The NEs stored at 4 ± 1 C exhibited higher increase in droplet size (coalescence) which might be attributed to the fact that at low temperature, NE droplets tend to aggregate/coalesce (Rahn-Chique et al, 2012). Jiang et al, have reported an increase in particle size up to 100 nm at room temperature in a three months stability study of nanoemulsion but they did not find any variation in the entrapment efficiency (Jiang et al, 2013).…”
Section: Stability Of Nesmentioning
confidence: 97%
“…Nano-emulsions can be prepared either through low-energy emulsification or high-energy emulsification methods or a combination of both (Koroleva and Yurtov, 2012). Due to their small droplet size, nano-emulsions are stable against sedimentation or creaming but prone to flocculation, coalescence and Ostwald ripening (Rahn-Chique et al, 2012). However, high kinetic stability of nano-emulsions can be obtained with proper choice of system components, composition and preparation method (Solans and Sole, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…56 The most widely used model for flocculation is the classical expression of Smoluchowski's equation 4,57,58 for hetero-aggregation. This expression is governed by two aspects, perikinetic (due to Brownian motion and diffusive adsorption, leading to attachment) and orthokinetic flocculation (transport of flocculants due to shear).…”
Section: Discussionmentioning
confidence: 99%